2019
DOI: 10.3390/biomedicines7030053
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Overview of the Antitumoral Actions of Leelamine

Abstract: For the last couple of decades, natural products, either applied singly or in conjunction with other cancer therapies including chemotherapy and radiotherapy, have allowed us to combat different types of human cancers through the inhibition of their initiation and progression. The principal sources of these useful compounds are isolated from plants that were described in traditional medicines for their curative potential. Leelamine, derived from the bark of pine trees, was previously reported as having a weak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…A natural compound found in the bark of pine trees is a diterpene amine called Leelamine ( 7 , Figure 2). It demonstrated cytotoxic activity against many cell lines including melanoma, prostate, and breast cancer 42 . Leelamine targets key oncogenic pathways including the receptor tyrosine kinase (RTK)‐Akt/signal transducer and activator of transcription 3 (STAT3)/ mitogen‐activated protein kinase (MAPK), and the Akt/mammalian target of rapamycin (mTOR) pathways 42 .…”
Section: Lipogenic Enzymes’ Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A natural compound found in the bark of pine trees is a diterpene amine called Leelamine ( 7 , Figure 2). It demonstrated cytotoxic activity against many cell lines including melanoma, prostate, and breast cancer 42 . Leelamine targets key oncogenic pathways including the receptor tyrosine kinase (RTK)‐Akt/signal transducer and activator of transcription 3 (STAT3)/ mitogen‐activated protein kinase (MAPK), and the Akt/mammalian target of rapamycin (mTOR) pathways 42 .…”
Section: Lipogenic Enzymes’ Inhibitorsmentioning
confidence: 99%
“…42 Leelamine targets key oncogenic pathways including the receptor tyrosine kinase (RTK)-Akt/signal transducer and activator of transcription 3 (STAT3)/ mitogen-activated protein kinase (MAPK), and the Akt/mammalian target of rapamycin (mTOR) pathways. 42 Recently, it was found that when prostate cancer is treated in vitro and in vivo with Leelamine, FA synthesis is disrupted by the downregulation of protein and/or mRNA expression of ACLY. 43 Compound 8 (Figure 2), also known as DCV (10,11-dehydrocurvularin), is a macrolide and fungus-derived natural-product recently connected with the ACLY target.…”
mentioning
confidence: 99%
“…However, additional work is necessary to systematically explore this possibility. Chemoprevention represents a worthwhile strategy for reducing the mortality and morbidity associated with prostate cancer [20][21][22] . The feasibility of prostate cancer chemoprevention has been explored clinically with 5α-reductase inhibitors (PCPT and REDUCE trials) as well as a novel combination of selenium and vitamin E (e.g., SELECT trial) [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that considerable efforts have been devoted to the therapeutic targeting of cMyc in prostate cancer [16] . Chemoprevention using natural products or synthetic chemicals is attractive for blunting the death and suffering from prostate cancer, but a clinically effective chemopreventive intervention for this malignancy is still lacking [17][18][19][20][21][22] . Leelamine (LLM) is one such phytochemical whose effectiveness has been tested against prostate and other cancers [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Closantel is halogenated salicylanilide with antiparasitic activity [57] and CD437 is synthetic retinoid that selectively induces apoptosis in cancer cells [58]. They were identified by this methodology as broad-spectrum ANT inhibitors, whereas natural diterpene amine known as anticancer compound leelamine [59] was found to be a modulator of ANT function. Authors suggest that, for example, selective inhibitors of ANT4, which are exclusively expressed in testis, may be optimized for use as male contraceptive agents [55].…”
Section: Human Adp/atp Carriermentioning
confidence: 99%